Rituální úpravy ženských pohlavních orgánů v diaspoře: k účinné ochraně dívek a dospívajících - MariaCaterina La Barbera (Gender a Výzkum)
Abstract: This article focuses on the ritual modifications of female genitalia. It compares interventions in male and female genitalia on the one hand and ritual and cosmetic female interventions on the other in order to show the double standard used in Western countries. The main goal is to call for a more complex articulation of gender at the intersection with migration status, ethnicity, and neo-colonial relations and to argue in favour of more effective ways to abandon practices that are dangerous for young girls.